English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can some1 answer or help me with these problems? I've been struggling with these equations 4 2 weeks now and still cant understand them. These are pratice problems that i have that i need to understand.These all need to be in order pair.


1) 3x - y = 10
-x + y = -4
a (3, -7)
b (-1, 3)
c (3, -1)
d(3, 1)

2) 3x - y = 9
2x + y = 6
a (3,0)
b (3,-18)
c (3,-1)
d (3,1)

3)-3x + y = -4
3x + y = -4
a (-4, 0)
b (4, 0)
c (0, 4)
d (0, -4)

4)2x – y = 4
3x + y = 1
a (1, 2)
b (-2, 1)
c (1, -2)
d (2, 1)

5) x + y = 10
x - y = 8
a (-1,11)
b (1,9)
c (9,1)
d(8,0)

6)3x - y = 9
2x + y = 6
a (3,0)
b (3,-18)
c (3,-1)
d (3,1)

these ones needs 2 be worked out.

7) 2a + 3b = -1
3a + 5b = -2

8)2x + 2y = -14
3x + y = -9

9)2x + 6y = 38
3x - 3y = -3

10)3x + 5y = 1
x + 4y = 5

11)x + y = -4
x - y = 2

12)x + y = 10
y = x + 8

13)3x + y = 5
4x - 7y = -10

14) y - 2x = -5
3y - x =5

2007-01-01 10:47:27 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

1)
3x - y = 10
-x + y = -4

2x = 6
x = 3

-3 + y = -4
y = -1

ANS : c. (3,-1)

---------------------------------------------------

2)
This is a repeat question

------------------------------------------

3)
-3x + y = -4
3x + y = -4

2y = -8
y = -4

-3x - 4 = -4
-3x = 0
x = 0

ANS : d. (0,-4)

------------------------------------------------

4)
2x – y = 4
3x + y = 1

5x = 5
x = 1

2(1) - y = 4
2 - y = 4
-y = 2
y = -2

ANS : c. (1,-2)

---------------------------------------------

5)
x + y = 10
x - y = 8

2x = 18
x = 9

9 + y = 10
y = 1

ANS : b. (1,9)

------------------------------------------

6)

3x - y = 9
2x + y = 6

5x = 15
x = 3

3(3) - y = 9
9 - y = 9
-y = 0
y = 0

ANS : a. (3,0)

----------------------------------------------------

7)
2a + 3b = -1
3a + 5b = -2

Multiply top by -3 and bottom by 2

-6a - 9b = 3
6a + 10b = -4

b = -1

2a + 3(-1) = -1
2a - 3 = -1
2a = 2
a = 1

ANS : (1,-1)


--------------------------------------

8)
2x + 2y = -14
3x + y = -9

3x + y = -9
y = -3x - 9

2x + 2(-3x - 9) = -14
x + (-3x - 9) -7
x - 3x - 9 = -7
-2x = 2
x = -1

y = -3(-1) - 9 = 3 - 9 = -6

ANS : (-1,-6)

-----------------------------------------------------

9)
2x + 6y = 38
3x - 3y = -3

multipy the bottom by 2

2x + 6y = 38
6x - 6y = -6

8x = 32
x = 4

2(4) + 6y = 38
8 + 6y = 38
6y = 30
y = 5

ANS : (4,5)

---------------------------------------------

10)
3x + 5y = 1
x + 4y = 5

x + 4y = 5
x = -4y + 5

3(-4y + 5) + 5y = 1
-12y + 15 + 5y = 1
-7y = -14
y = 2

x = -4(2) + 5 = -8 + 5 = -3

ANS : (-3,2)

-------------------------------------------

11)
x + y = -4
x - y = 2

2x = -2
x = -1

-1 + y = -4
y = -3

ANS : (-1,-3)

------------------------------------------------

12)
x + y = 10
y = x + 8

x + (x + 8) = 10
x + x + 8 = 10
2x + 8 = 10
2x = 2
x = 1

y = 1 + 8 = 9

ANS : (1,9)

----------------------------------

13)
3x + y = 5
4x - 7y = -10

3x + y = 5
y = -3x + 5

4x - 7(-3x + 5) = -10
4x + 21x - 35 = -10
25x = 25
x = 1

y = -3(1) + 5 = -3 + 5 = 2

ANS : (1,2)

------------------------------------------------

14)
y - 2x = -5
3y - x =5

y - 2x = -5
y = 2x - 5

3(2x - 5) - x = 5
6x - 15 - x = 5
5x = 20
x = 4

y = 2(4) - 5 = 8 - 5 = 3

ANS : (4,3)

2007-01-01 15:58:12 · answer #1 · answered by Sherman81 6 · 0 0

Hint:

3x - y = 10 3x - y = 10
-x + y = -4 = + (-3x + 3y = -12)
2y = -2 y = -1

or y = -4 + x
using substitution for the first first equation
3x - (-4 +x) =10
3x +4 - x =10
2x + 4 =10
2x = 6
x = 3

2007-01-01 11:10:53 · answer #2 · answered by Michael E 2 · 0 0

This very simple!
Given: 3x - y = 10 and -x + y = -4
take a (3, -7)
Plug x=3 and y=-7 in both of the eq. and see which one works!
If this choice don't work try others.

Other way is to solve the eqs and find x and y!

3x - y = 10.................(1)
(-x + y = -4) X 3
-3x+3y=-12...............(2)

add (1) and (2)

2y=-2
y=-1

so the answer is c!!!!

I hope this helps!!

2007-01-01 11:13:11 · answer #3 · answered by smart-crazy 4 · 0 0

5x + 2y = 15 -5x - 2y = -5 _____________ 0 = 10 you sparkling up utilizing combining words, you upload both equations. 0=10 potential this device of equation has no answer in any respect, because the slopes of both strains are a similar, in different words are parallel strains, so there is not element of interception

2016-12-01 10:03:18 · answer #4 · answered by Anonymous · 0 0

I will not do all these but I can easily help you if you e-mail me. Solve for x or y in one of the equations so that x=... or y=... then fill the "..." in for the x or y in the other equation and solve for the other variable and using that answer fill it into one of the original equations then you should have x and y.

2007-01-01 10:58:16 · answer #5 · answered by Dirk D 2 · 0 0

For shame: posting multiple choice questions...

2007-01-01 10:57:15 · answer #6 · answered by modulo_function 7 · 0 0

fedest.com, questions and answers